2020
DOI: 10.1017/s1092852920000140
|View full text |Cite
|
Sign up to set email alerts
|

Impact of economic crisis on mental health: a 10-year challenge

Abstract: The worldwide economic crisis of the last decade, and still unresolved, led to a great recession involving all major economies. Since economic factors may influence mental wellbeing, not surprisingly a rise in poor mental health was observed in different countries, while representing a great challenge to psychiatric interventions. This paper aims at reviewing the available English literature focusing on the impact of the current economic crisis on mental health, with a special focus on depression and suicide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 52 publications
0
26
0
2
Order By: Relevance
“…Despite existing data about adults, there is little data about adolescents' psychiatric disorders during economic crises. Periods of economic crisis are reportedly associated with an increase in suicides, depression, anxiety, and addiction disorders in adults (Gili et al, 2013;Marazziti et al, 2020;Uutela, 2010;Silva et al, 2020). Interestingly, some authors reported that income reduction was the highest predicting factor of psychological disorder development during recovery following the 2003 SARS outbreak in Beijing, China (Mihashi et al, 2009).…”
Section: Economic Crisismentioning
confidence: 99%
“…Despite existing data about adults, there is little data about adolescents' psychiatric disorders during economic crises. Periods of economic crisis are reportedly associated with an increase in suicides, depression, anxiety, and addiction disorders in adults (Gili et al, 2013;Marazziti et al, 2020;Uutela, 2010;Silva et al, 2020). Interestingly, some authors reported that income reduction was the highest predicting factor of psychological disorder development during recovery following the 2003 SARS outbreak in Beijing, China (Mihashi et al, 2009).…”
Section: Economic Crisismentioning
confidence: 99%
“…14 Financial strain also has a cumulative effect on suicide attempts and ideation, with greater financial strain causing higher prevalence of suicide. 15 Potential pathways to depression from economic recessions include unemployment, 16 increased job stress, staff reduction and decreased wages, 17 as well as cuts to mental health services. 18 Lower socioeconomic indicators are associated with greater risk of mental illness 19 20 ; conversely, wealth is associated with improved health, including mental health.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as economic inequality may heighten status anxiety, which then may negatively affect well-being in the population (Wilkinson and Pickett, 2009), future research could also examine the possible mediating role of status anxiety in reactions to pay inequalities in the workplace, perhaps especially among those lower in status (e.g., Card et al, 2012). Similarly, as economic crises are consistently linked to worse psychological well-being (Van Hal, 2015;Martin-Carrasco et al, 2016;Marazziti et al, 2020), it may be worthwhile to explore how the relationship between status anxiety and lower job satisfaction may be affected by such societal events.…”
Section: Discussionmentioning
confidence: 99%